DETERMINANTS OF POVERTY LEVEL IN INDONESIA - Mutmainnah Mutmainnah; Hamid Paddu; Hamrullah (SEAN Institute, 2022)
This study observes that there is a slowdown in poverty reduction in Indonesia, so that in order to realize the achievement of no poverty in 2030 it is necessary to carry out further research related to the determinants of poverty in Indonesia. Researchers used panel data from 34 provinces in Indonesia for the 2015-2020 period. The model used is panel data regression using panel data regression analysis. The results of the study are that government spending directly has a significant effect on poverty and indirectly through unemployment has a significant effect but government spending does not have a significant effect on poverty through economic growth, investment has a significant effect on poverty but indirectly both through growth and unemployment have no significant effect,